Does EMLA cream application interfere with the success of venipuncture or venous cannulation? A prospective multicenter observational study. - Schreiber, S; Ronfani, L; Chiaffoni, G P; Matarazzo, L; Minute, M; Panontin, E; Poropat, F; Germani, C; Barbi, E (Eur J Pediatr, 2013)
UNLABELLED: Venipuncture and intravenous cannulation are the most common painful procedures performed on children. The most widely used topical anesthetic is eutectic mixture of local anesthetics (EMLA). EMLA use is associated with a transient cutaneous vasoconstriction which can make it difficult to identify veins. We assessed with a prospective, multicenter, observational study whether EMLA interferes with venipuncture and intravenous cannulation. The primary study outcome was a success at first attempt in the course of venipuncture or venous cannulation. The study enrolled 388 children; 255 of them received EMLA and 133 did not. Eighty-six percent of procedures were successful at the first attempt in the EMLA group and 76.7 % in the no EMLA group. CONCLUSION: In this study, EMLA use did not interfere with the success of venipuncture or venous cannulation in children.
Keywords: Anesthetics, Local; Catheterization, Peripheral; Child; Child, Preschool; Female; Humans; Lidocaine; Logistic Models; Male; Ointments; Phlebotomy; Prilocaine; Prospective Studies; Vasoconstriction